COGNITIVE FUNCTION ASPECTS IN HIV-ASSOCIATED CEREBRAL TOXOPLASMOSIS: A CASE REPORT - Lasta Arshinta; Anak Agung Ayu Putri Laksmidewi; Ni Wayan Nurlina Ekasari; Dian Kusumastuti Anggraeni Putri; Gede Suputra; Bagus Ngurah Mahasena Putera Awatara (MNJ (Malang Neurology Journal), 2024)
HIV-associated cerebral toxoplasmosis may lead to cognitive function impairment through accumulation of β-amyloid plaques and Tau protein which cause damage, inflammatory and oxidative processes in the brain. A 40-year-old, Balinese, right-handed female patient, came with chief complaint of three times of seizure before admission. After the seizures stopped, the patient was fully conscious again. Since the last 2 months, the patient seemed more confused and spoke a little slower. The patient also often repeated a story about something and forgot that she had already told it. The patient has a known history of HIV infection in the past 3 months before admission, she had taken anti-retroviral agents but she stopped them by herself since last 1 month. Anti-Toxoplasma IgG antibody showed reactive results and CD-4 of 62 cells/µL. The results of the overall cognitive function examination found mild cognitive impairment with activities that required mild assistance. HIV-associated neurocognitive disorders (HAND) are still a challenge to study, and the importance of improving patient cognitive function to maintain or increase aspects of independence and quality of life is a target in the care of HIV patients, especially patients with HIV-associated cerebral toxoplasmosis infection.